Men to boys : the making of modern immaturity - Cross, Gary S. (Columbia University Press, 2008)
Publisher's description -- Adam Sandler movies, HBO's Entourage, and such magazines as Maxim and FHM all trade in and appeal to one character -- the modern boy-man. Addicted to video games, comic books, extreme sports, and dressing down, the boy-man would rather devote an afternoon to Grand Theft Auto than plan his next career move. He would rather prolong the hedonistic pleasures of youth than embrace the self-sacrificing demands of adulthood. When did maturity become the ultimate taboo? Men have gone from idolizing Cary Grant to aping Hugh Grant, shunning marriage and responsibility well into their twenties and thirties. Gary Cross, renowned cultural historian, identifies the boy-man and his habits, examining the attitudes and practices of three generations to make sense of this gradual but profound shift in American masculinity. Cross matches the rise of the American boy-man to trends in twentieth-century advertising, popular culture, and consumerism, and he locates the roots of our present crisis in the vague call for a new model of leadership that, ultimately, failed to offer a better concept of maturity. Cross does not blame the young or glorify the past. He finds that men of the "Greatest Generation" might have embraced their role as providers but were confused by the contradictions and expectations of modern fatherhood. Their uncertainty gave birth to the Beats and men who indulged in childhood hobbies and boyish sports. Rather than fashion a new manhood, baby-boomers held onto their youth and, when that was gone, embraced Viagra. Without mature role models to emulate or rebel against, Generation X turned to cynicism and sensual intensity, and the media fed on this longing, transforming a life stage into a highly desirable lifestyle. Arguing that contemporary American culture undermines both conservative ideals of male maturity and the liberal values of community and responsibility, Cross concludes with a proposal for a modern marriage of personal desire and ethical adulthood